The Greig cephalopolysyndactyly syndrome - Biesecker, Leslie G (BioMed Central, 2008)
The Greig cephalopolysyndactyly syndrome (GCPS) is a pleiotropic, multiple congenital anomaly syndrome. It is rare, but precise estimates of incidence are difficult to determine, as ascertainment is erratic (estimated range 1–9/1,000,000). The primary findings include hypertelorism, macrocephaly with frontal bossing, and polysyndactyly. The polydactyly is most commonly preaxial of the feet and postaxial in the hands, with variable cutaneous syndactyly, but the limb findings vary significantly. Other low frequency findings include central nervous system (CNS) anomalies, hernias, and cognitive impairment. GCPS is caused by loss of function mutations in the GLI3 transcription factor gene and is inherited in an autosomal dominant pattern. The disorder is allelic to the Pallister-Hall syndrome and one form of the acrocallosal syndrome. Clinical diagnosis is challenging because the findings of GCPS are relatively non-specific, and no specific and sensitive clinical have been delineated. For this reason, we have proposed a combined clinical-molecular definition for the syndrome. A presumptive diagnosis of GCPS can be made if the patient has the classic triad of preaxial polydactyly with cutaneous syndactyly of at least one limb, hypertelorism, and macrocephaly. Patients with a phenotype consistent with GCPS (but which may not manifest all three attributes listed above) and a GLI3 mutation may be diagnosed definitively with GCPS. In addition, persons with a GCPS-consistent phenotype who are related to a definitively diagnosed family member in a pattern consistent with autosomal dominant inheritance may be diagnosed definitively as well. Antenatal molecular diagnosis is technically straightforward to perform. Differential diagnoses include preaxial polydactyly type 4, the GCPS contiguous gene syndrome, acrocallosal syndrome, Gorlin syndrome, Carpenter syndrome, and Teebi syndrome. Treatment of the disorder is symptomatic, with plastic or orthopedic surgery indicated for significant limb malformations. The prognosis for typically affected patients is excellent. There may be a slight increase in the incidence of developmental delay or cognitive impairment. Patients with large deletions that include GLI3 may have a worse prognosis. The Article is a work of the United States Government. Title 17 U.S.C 5 105 provides that copyright protection is not available for any work of the United States Government in the United States. The United States hereby grants to anyone a paid-up, nonexclusive, irrevocable worldwide license to reproduce, prepare derivative works, distribute copies to the public and perform publicly and display publicly the work, and also retains the nonexclusive right to do all of the above for or on behalf of the United States.